Determinants of Public Trust in Vaccines in the Aftermath of a Global Health Emergency - Jumah, Hani Mohammed Ali; Alkhthami, Abdullah Mohammed; Albedaiw, Reem Asaad; Altayyari, Sultan Atiah Allah; Essa, Fatinah Saud; Alyamani, Ahmad Fouad Ahmad; Ahmed, Suhael; Kumar, Sowmya M; Almalki, Turki Saleh; Alharshani, Essam; et al. (Journal of Cultural Analysis and Social Change, 2025)
Public trust in medicines and vaccines is a critical determinant of public health outcomes, particularly in the aftermath of global health crises such as the COVID-19 pandemic. Trust influences vaccine uptake, adherence to medical treatments, and acceptance of health recommendations from authorities. However, evidence suggests that confidence in vaccines and routine medical interventions fluctuated significantly during and after the COVID-19 crisis, with booster uptake decreasing in many countries and skepticism rising due to misinformation and institutional distrust. This scientific analysis synthesizes findings from recent studies to analyze the determinants of public trust, the impact of crisis communication, and the challenges associated with restoring trust after a global health emergency. The review highlights the need for transparent communication, strong institutional credibility, and culturally contextualized trust-building strategies.